What's Ahead for 2007? Knowledge@Wharton Network Surveys the Globe - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2006)
On the financial front, 2006 has been a pretty good year all around. Stock markets in many countries have rallied, energy prices have fallen, inflation is relatively low and growth in GDP ranges from respectable to robust. But the economies of most countries also face a number of threats -- some predictable, some not -- that could derail recent gains in our increasingly connected global markets. What's ahead for 2007 in the U.S., India, Europe, Latin America, China and other parts of the world? We offer a roundup of reports from the Knowledge@Wharton Network, including India Knowledge@Wharton, Universia Knowledge@Wharton and China Knowledge@Wharton.